Engineering the Future of Outreach - Emily Dommermuth; Megan Welsh (Issues in Science and Technology Librarianship, 2021)
While academic libraries strive to meaningfully engage their campus communities, it can be hard to imagine new and creative outreach strategies. InfoMotion, a customized tricycle, is the University of Colorado Boulder Libraries’ “vehicle” to meet patrons where they are and embed ourselves in the campus community. InfoMotion was mobile and eye-catching, but it was cumbersome as we navigated campus pathways. The authors discuss their institutional context and describe an impactful partnership with engineering students to design an electric-assist system for InfoMotion. This collaboration resulted in a more user-friendly way for Libraries personnel to engage with the campus community, and helped the authors learn about student information needs while building relationships with engineering faculty and students.